Dampak Program Desa Wisata Danau Anak Laut Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat - Rahmawati; Kristina Situmeang, Marini (JAROW: Journal of Ar-Raniry on Social Work, 2024)
The tourism sector is a sector that has the potential to be developed as a source of original regional income. The existence oftourism is considered as a regional potential to increase income. The community is involved in managing regional tourism potential. One of the villages that was develoved as a tourist village is Gosong Telaga Barat village. This research aims to determine the Management of Tourism Villages and the Impact of the Tourism Village Program in Improving the Economic Welfare of the Community of Gosong Telaga Barat Village, North Singkil District, Aceh Singkil Regency. This research uses descriptive qualitative research methods. Through observation, interviews and documentation with 6 informants. The results of the research show that development in the management of tourist villages are concidered good. Community readiness in managing tourist villages in seen from the aspects of procurement of funds and land,development of fasilities and infrastructure, promotion of tourist attractions, readiness of the community as business actors. In this case, it shows that the tourist village has a pissitive impact on the economic development of the community in Gosong Telaga Barat Village, including increasing community income, opportunities for employment and business, increasing ounership and management, increasing income.